2020
DOI: 10.1016/j.jde.2019.11.091
|View full text |Cite
|
Sign up to set email alerts
|

Bounds for invariance pressure

Abstract: This paper provides an upper for the invariance pressure of control sets with nonempty interior and a lower bound for sets with finite volume. In the special case of the control set of a hyperbolic linear control system in R d this yields an explicit formula. Further applications to linear control systems on Lie groups and to inner control sets are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Invariance pressure, as a generalization of invariance entropy, was first introduced by Colonius, Santana, and Cossich [8,4]. Recently, the same authors in [7] obtain some bounds of invariance pressure and get an explicit formula for hyperbolic linear control systems. Zhong and Huang [19] introduced a version of invariance pressure in a way resembling Hausdorff dimension, which is called Bowen invariance pressure.…”
Section: (Communicated By Xiangdong Ye)mentioning
confidence: 99%
“…Invariance pressure, as a generalization of invariance entropy, was first introduced by Colonius, Santana, and Cossich [8,4]. Recently, the same authors in [7] obtain some bounds of invariance pressure and get an explicit formula for hyperbolic linear control systems. Zhong and Huang [19] introduced a version of invariance pressure in a way resembling Hausdorff dimension, which is called Bowen invariance pressure.…”
Section: (Communicated By Xiangdong Ye)mentioning
confidence: 99%
“…Theorem 15 Consider the control system given by (3) and suppose that the system without control restriction is controllable.…”
Section: Lemma 14 Ifmentioning
confidence: 99%
“…Theorems 18 and 20. The proof uses arguments from [3] which in turn are based on a construction by Kawan [8,Theorem 4.3], [9, Theorem 5.1] (for the discrete-time case cf. also [9,Remark 5.4] and Nair, Evans, Mareels, Moran [12,Theorem 3]).…”
Section: Invariance Pressure For Linear Systemsmentioning
confidence: 99%
“…Measuretheoretic versions of invariance entropy have been considered in Colonius [4] and Wang et al [15]. Invariance pressure has been analyzed in Colonius et al [1][2][3]. In Zhong and Huang [18] it is shown that several generalized notions of invariance pressure fit into the dimensiontheoretic framework due to Pesin.…”
Section: Introductionmentioning
confidence: 99%